Risk of Chemical Pollution in Olifants River Basin, South Africa: Human Health Implications - Abraham Addo-Bediako (Limnological Review)
Chemical pollution in freshwater ecosystems poses a significant environmental threat, often hindering access to safe drinking water for human populations. The Olifants River Basin in South Africa is particularly vulnerable due to escalating mining and agricultural activities, and domestic waste discharged into the rivers. In this study, the risk posed to humans by exposure to potentially toxic elements (PTEs) in water from two rivers, the Blyde and Steelpoort, was assessed. Water samples were collected from upstream, midstream, and downstream locations of these rivers, and the concentrations of eight PTEs (Arsenic, Cadmium, Chromium, Iron, Manganese, Nickel, Lead, and Zinc) were determined using inductively coupled plasma-optical emission spectrophotometry. Furthermore, two pathways of exposure, direct ingestion and dermal absorption, were used to evaluate their potential impacts on human health. The findings indicate that direct ingestion poses a greater risk to human health compared to dermal absorption. While PTEs may pose little non-carcinogenic risk for adults, higher risk was observed in children. This is an indication that children are at higher risk using water from the rivers, sometimes without any form of treatment. When carcinogenic risks (CRs) were computed for both adults and children for As, Cr, Ni, and Pb levels, the CR values were above the threshold limit, except for Pb, indicating a potential carcinogenic risk. This study underscores the need for regular monitoring of chemical pollution, and the implementation of effective mitigation strategies to safeguard both river ecosystems and human health, including proper treatment of water for domestic and agricultural purposes.